Ukrajinski in ruski jezik v Ukrajini po desetih letih neodvisnosti - Besters-Dilger, Juliane (Slavistična revija, 2001)
Although at the time of 1989 census Ukrainians represented 72,6% of Ukrainian population, only 64% of population considered Ukrainian as their mother tongue and only 43,9% of population gave it priority in communication to the more prestigious Russian. Since then the independance of Ukraine was declared in 1991, language legislation was passed as early as 1989, and Ukrainian costitution was adopted in 1996, all of which was supposed to have stimulated the use and strenthened the legal status and prestige of the Ukrainian language. However, after the years only modest success in Ukrainization has been seen, i.e., only in radio and television broadcasting, school and pre-school education.
Keywords: 1989-; bilingvizem; jezikovna politika; Russian; ruščina; sociolinguistics; sociolingvistika; Ukraine; Ukrajina; ukrajinizacija; ukrajinščina